Impact of Radiodermatitis on body aesthetics in head and neck cancer patients - Bárbara de Sousa Cabral; Paula Elaine Diniz dos Reis; Elaine Barros Ferreira (Universidade Federal de Santa Maria, 2021)
Objective: to describe the impact of radiodermatitis on body aesthetics in patients with head and neck cancer undergoing radiotherapy. Method: this is an exploratory descriptive case series study conducted at the radiotherapy outpatient clinic of a teaching hospital. Ten patients with head and neck cancer who underwent radiotherapy from 2015 to 2017 were included. Data collection was performed with an instrument designed for this purpose and through photographic record. Data was analyzed descriptively, presenting the calculation of frequency. Results: all patients presented characteristic signs of radiodermatitis, mainly the clinical signs of epilation (in men), hyperpigmentation and dry scaling, which affect body aesthetics. Conclusion: the body aesthetics of the followed patients was altered as a result of the clinical signs of radiodermatitis. It is important to evaluate these changes in patients with head and neck cancer undergoing radiotherapy.